Keragaman Genetik dan Hubungan Kekerabatan Ayam Lokal Berdasarkan Penanda RAPD - Mery Wintari; Made Pharmawati; Ngurah Intan Wiratmini (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2019)
Indonesian local chicken is one kind of germplasm that has been utilized by the community for various needs, such as consumption, ceremonial, collection, and cockfighting. To maintain its sustainability, an inventory of genetic diversity can be made using molecular markers. This study aimed to determine the genetic diversity and relationship between four Indonesian local chickens: ayam kampung, ayam ketawa, ayam kate lokal, and ayam bekisar kangean, based on RAPD marker. DNA was extracted from blood samples of 12 local chickens consisting of 3 ayam kampung, 3 ayam ketawa, 3 ayam kate lokal, and 3 ayam bekisar kangean using Genetic DNA Mini Kit (Tissue) Geneaid. The PCR-RAPD analysis was performed using 6 primers, OPA 04, OPB 08, OPB 12, OPC 16, OPH 01, and OPH 03. The product of PCR-RAPD was electrophoresed using 1,5% agarose in 1x TAE buffer. The results showed that the similarity value of 12 local chickens using RAPD ranged from 0% to 100%. The relationship between 12 local chickens using RAPD marker indicated that the chickens in the same morphology were not clustered in the same group. This suggests that the same group of chickens phenotypically does not necessarily have the same genotype. Keywords: Local Chicken, PCR-RAPD